MOTIVASI, KOMUNIKASI DAN SEMANGAT KERJA PEGAWAI - Freitas Belo, Maria Imaculada (Jurnal Ilmu Administrasi Negara, 2014)
Motivation, Communication and Employee Morale. This study aims to determine the effect of motivation and communication on employee morale Kupang District Office. Study population was all employees as well as the sample (census), which amounts to as many as 36 people. Data collection techniques using koesioner, interviews and observations. Data were analyzed using simple correlation. The results showed that the partially and simultaneously, the influence of motivation and communication on employee morale is positive and significant. The results of the analysis coefficient determinant (R2) indicates that the contribution of variable motivation and communication on employee morale sizeable 73.6% and the remaining 26.4% is influenced by other variables. The role of communication between the leadership of subordinate variables is an important variable in improving employee morale. Keywords: motivation, communication, morale, leadership.